Między kosmopolityzmem a nazizmem – konteksty przestrzeni symbolicznych czterech filmów nakręconych przez niemieckiego operatora Franza Weihmayra - Mazur, Daria (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The paper is a comparative analysis of the circumstances influencing symbolic spaces in four movies by Franz Weihmayr in the years 1931–1942: Dzikie Pola [Wild Fields], Halutzim, La Habanera and The Great Love. The analysis allows for delineating the development of the German cinematographer Franz Weihmayr’s career, which, in the context of historical-political and ideological-artistic circumstances, can serve as an example of a broader phenomenon: a particular fluctuation of choices made by German cinematographers over the Weimar, Nazi, and post-war periods. This analysis is of pioneering importance because of the paucity of publication heretofore dedicated to Weihmayr’s works, who at the time worked together with, among others, Leni Riefenstahl, Frank Wysbar, and Hans Detlef Sierck, as well as Polish directors, such as Józef Lejtes and Aleksander Ford. The framework for semiotic analyses of the symbolic spaces of the movies mentioned above are two groups of contexts connected with ideas stemming from contradictory bases: the idea of cosmopolitism and the idea of Nazism.